KUALITAS MAKANAN TRADISIONAL DENDENG DAUN UBI DI KOTA BUKIT TINGGI - Namira, Dea; Asnur, Lise (Journal of Food Technology and Agroindustry, 2024)
A tourist destination has a list and experiences of visitors regarding intangible cultural heritage, such as experiences, local specialty products, cultural performances, etc. Cultural attractions can be in the form of folklore, the appeal of a building, unique cultural performances, religion, and the allure of traditional foods. Based on observations and interviews that the researcher has conducted using two different types of cassava leaf jerky, they obtained different qualities, which tend to make consumers uninterested in buying. The purpose of this research is to obtain the expected quality of traditional food, assessed based on color, taste, shape, texture, and aroma. The method used is qualitative-descriptive, and the results of this research indicate that homemade cassava leaf jerky without a brand is the most favored.